PENGARUH STRATEGI TINGKAT BISNIS, FREE CASH FLOW, LEVERAGE, PROFITABILITAS, SALES GROWTH DAN RISIKO LITIGASI TERHADAP MANAJEMEN LABA (Studi Empiris pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Tahun 2016-2018) - Riski, Lindarti; Kamaliah, Kamaliah; Pipin, Kurnia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
The purpose of this research is to examine the effect of busines level strategy, free cash flow, leverage, profitability, sales growth and litigation risk on the earning management. The population is a banking company listed on the Indonesia Stock Exchange in 2016-2018. Total sample is 39 companies based on Purposive Sampling methode. Technique of data analysis Structural Equation Modeling (SEM) using Partial Least Squares (PLS) version 6.0 for Windows as data processing software program. The result show that (1) Busines Level Strategy effect on the Earning Management, (2) Free cash flow effect on the Earning Management, (3) Leverage effect on the Earning Management, (4) Profitability effect on the Earning Management, (5) Sales growth effect on the Earning Management, (6) Litigation Risk effect on the Earning Management. Based on the calculation of coefficient determination (R2) was 0.821 which means 82.1% of the independent variables in this study can affect the dependent variable. While the remaining 17.9% is influenced by other independent variable that are not observed in this study. Keyword: earning management, business level strategy, free cash flow, leverage, profitability, sales growth, litigation risk.